Catalytic asymmetric C–N cross-coupling towards boron-stereogenic 3-amino-BODIPYs - Baoquan Zhan; Li-Qing Ren; Jiayi Zhao; Hua Zhang; Chuan He (Nature Communications)
Abstract 3-Amino boron dipyrromethenes (BODIPYs) are a versatile class of fluorophores widely utilized in live cell imaging, photodynamic therapy, and fluorescent materials science. Despite the growing demand for optically active BODIPYs, the synthesis of chiral 3-amino-BODIPYs, particularly the catalytic asymmetric version, remains a challenge. Herein, we report the synthesis of boron-stereogenic 3-amino-BODIPYs via a palladium-catalyzed desymmetric C–N cross-coupling of prochiral 3,5-dihalogen-BODIPYs. This approach features a broad substrate scope, excellent functional group tolerance, high efficiency, and remarkable enantioselectivities, under mild reaction conditions. Further stereospecific formation of chiral 3,5-diamino-BODIPYs, along with an investigation into the photophysical properties of the resulting optical BODIPYs are also explored. This asymmetric protocol not only enriches the chemical space of chiroptical BODIPY dyes but also contributes to the realm of chiral boron chemistry.